The Effectiveness of Learning Programming Language Online: Student Perceptions and Performance - Nordin, Noradila (UUM Press, 2021)
This study aims to explore the effectiveness of learning programming language using online-based learning compared to traditional-based learning towards undergraduate students in Universiti Utara Malaysia (UUM). Similar types of learning materials are used with additional forms of assessments to substitute the final exam. The main difference is in the learning approaches which have been switched to online based via various platforms depending on the suitability and preference by the students. This research focuses on identifying and analyzing certain aspects from the students’ perceptions, which are the students’ (1) learning preference; (2) learning engagement; (3) learning assessment, and in terms of their overall (4) satisfaction towards the learning process. This study uses a quantitative approach through the questionnaire as the survey instrument, involving 31 students. The data is analyzed using descriptive statistics (percentage frequency distribution, mean, and standard deviation). Findings show promising results in online-based learning as 48.39% obtained marks above 80% in Lab Test 2, which is doubled compared to the previous test, Lab Test 1, 25.81%. This indicates that while students prefer traditional-based learning, they are able to perform better through online-based learning.